Analisis Tegangan City Electric Car Torsi Beam Suspension Menggunakan Metode Finite Element Model (FEM) - Sigit Setijo Budi; Agus Suprihadi; Syarifudin Syarifudin (P3M Politeknik Negeri Cilacap, 2021)
The torsion beam is one of the most important parts of an electric car. The torsion beam can accept the loading of vehicle structures statically and dynamically. The movement of the vehicle, such as turning, turning with a bumpy road contour, affects the stress limit that the torsion beam can support. This study aims to simulate the effects of shifts such as deflection and stress on the use of a torsion beam suspension. The method used is a loading simulation using the Finite Element Model (FEM) model. The results showed that the maximum deflection effect occurred in the 2000N loading of 1.5347 mm, while the maximum stress effect occurred in the 2000N loading of 2342.57N.